المداينات المصرفية المعاصرة وإشكالية الربا الخفي : عرض وتقويم - جعفر، عبد القادر جعفر (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
Debt-based transactions are widely spread nowadays. This is mainly due credit institutions practices, and foreign interest-based regulations based on explicit riba that permeated jurisdictions of Muslim countries. This study is conducted to address the ambiguity that may arise as to the difference between explicit (jaliyy) and implicit (khafiyy) riba featuring some of the contemporary Islamic financial transactions. This research aims at tracing the kinds of debts involving Riba, be it explicit or implicit via the mechanism of hiyal (legal stratagems). This required the clarification of the principles of debt financing, and the principles of Riba in Islamic jurisprudence, with a focus on interest-based arguments, through classical and contemporary examples. This research applies methods that combine induction, content analysis, and criticism. This approach is appropriate for tracking the true nature of the issues related to this topic, issues that are scattered in many papers and electronic references. The research concluded that Riba may be hidden in a direct credit chatges, penalties for late payment or settlement of debts, and charging the debtor the depreciation value of the currency agreed to be used in settlement, except in a few cases. Further, whenever it becomes impossible to apply the Shariah contract using its established terminologies, the transaction becomes suspicious and thus may be usurious. The riba becomes explicit when the deferred price is higher than the spot price unless the increment of the price when deferred is separated from the principle amount. Also, The riba would not be hidden when the debtor is granted rebate on early payment with prior agreement between the creditor and the debtor.